2003
DOI: 10.1016/s0194-5998(03)00477-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of n3 nodal head and neck squamous cell carcinoma

Abstract: Our treatment outcomes, particularly those in the group receiving postoperative radiotherapy, were similar to other studies. The prognosis of N3 neck disease was poor but improved with radiotherapy, particularly postoperative radiotherapy. The role of definitive chemotherapy and/or radiotherapy and salvage surgery is difficult to evaluate as the results are inconsistent and the available data are limited. Future studies in particular with quality of life assessment are needed to evaluate the management of N3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Those with less than five pathologically positive nodes, despite having N3‐stage disease, had a 5‐year DFS of over 96% (95% CI: 88%–100%); whereas, those with five or more positive nodes had a 5‐year DFS of 64% (95% CI: 38%–90%). Finally, the addition of adjuvant therapy is a critical feature of management of patients with bulky nodal disease, and surgery alone has been shown to result in high regional recurrence rates …”
Section: Discussionmentioning
confidence: 99%
“…Those with less than five pathologically positive nodes, despite having N3‐stage disease, had a 5‐year DFS of over 96% (95% CI: 88%–100%); whereas, those with five or more positive nodes had a 5‐year DFS of 64% (95% CI: 38%–90%). Finally, the addition of adjuvant therapy is a critical feature of management of patients with bulky nodal disease, and surgery alone has been shown to result in high regional recurrence rates …”
Section: Discussionmentioning
confidence: 99%
“…Chan et al 19 classified patients into four groups depending on the treatment received: (i) those treated with neck dissection followed by radiotherapy; (ii) those who had a pre-operative radiotherapy followed by planned neck dissection surgery; (iii) those who were treated only with neck dissection surgery due to a refusal to have radiotherapy or who died before radiotherapy; and (iv) those who had preor postoperative chemotherapy with or without chemotherapy. All patients had squamous cell carcinoma of the head and neck and advanced neck disease (N3).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A combination of radical neck dissec- Surgery and postoperative radiotherapy ---3 8.9 Carvalho et al 19 Surgery and postoperative radiotherapy 69.2 -2 6.9 -Smeele et al 20 Surgery and postoperative radiotherapy -4 91 -- Table 1 Summary of disease-specific survival rates from the literature tion, extended radical neck dissection and selective neck dissections. In 88.9% of these patients, adjuvant radiotherapy was performed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A retrospective non- randomized study showed that the 5-year survival rate was significantly higher for those who had postoperative radiotherapy (38.9%) compared with patients who had pre-operative radiotherapy (9.1%) and those having surgery alone (0%). They were unable to evaluate the role of definitive chemotherapy and/or radiotherapy and salvage surgery as the results were inconsistent and the available data was limited [44]. …”
Section: Management Of Positive Neck Nodesmentioning
confidence: 99%